Novel chimeric antigen receptor T cell-based immunotherapy: a perspective for triple-negative breast cancer - Geng, Peizhen; Chi, Yuhua; Yuan, Yuan; Yang, Maoquan; Zhao, Xiaohua; Liu, Zhengchun; Liu, Guangwei; Liu, Yihui; Zhu, Liang; Wang, Shuai (Frontiers in Cell and Developmental Biology, 2023)
Triple-negative breast cancer (TNBC) is highly aggressive and does not express estrogen receptor (ER), progesterone (PR), or human epidermal growth factor receptor 2 (HER2). It has a poor prognosis, and traditional endocrine and anti-HER2 targeted therapies have low efficacy against it. In contrast, surgery, radiotherapy, and/or systemic chemotherapy are relatively effective at controlling TNBC. The resistance of TNBC to currently available clinical therapies has had a significantly negative impact on its treatment outcomes. Hence, new therapeutic options are urgently required. Chimeric antigen receptor T cell (CAR-T) therapy is a type of immunotherapy that integrates the antigen specificity of antibodies and the tumor-killing effect of T cells. CAR-T therapy has demonstrated excellent clinical efficacy against hematological cancers. However, its efficacy against solid tumors such as TNBC is inadequate. The present review aimed to investigate various aspects of CAR-T administration as TNBC therapy. We summarized the potential therapeutic targets of CAR-T that were identified in preclinical studies and clinical trials on TNBC. We addressed the limitations of using CAR-T in the treatment of TNBC in particular and solid tumors in general and explored key strategies to overcome these impediments. Finally, we comprehensively examined the advancement of CAR-T immunotherapy as well as countermeasures that could improve its efficacy as a TNBC treatment and the prognosis of patients with this type of cancer.